2010
DOI: 10.3109/00016340903280966
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section in relation to self‐esteem and parenting among new mothers in southwestern Nigeria

Abstract: CS in Nigerian women is associated with lowered self-esteem and predicts poor parenting self-efficacy in the postnatal period. Psychological support and techniques to improve self-esteem and parenting should be incorporated into the management of women having CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Our data also showed that some women stayed away from some formal facilities and opted for alternative home births in fear of "unnecessary" caesarian section whenever their labor did not progress well due to perceived inadequate care or health-care provider engagement at these facilities. Just like our study, other scholars have reported perceptions on caesarian sections in some communities as socially or culturally unacceptable and a limiting factor to how many children one was destined to have (26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 59%
“…Our data also showed that some women stayed away from some formal facilities and opted for alternative home births in fear of "unnecessary" caesarian section whenever their labor did not progress well due to perceived inadequate care or health-care provider engagement at these facilities. Just like our study, other scholars have reported perceptions on caesarian sections in some communities as socially or culturally unacceptable and a limiting factor to how many children one was destined to have (26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 59%
“…A total of 30 study participants with differing experiences of pregnancy and antenatal care; 15 women who delivered from their homes and 15 who delivered from a health facility were purposively selected from the 10 villages within 20 km from of a referral hospital with the help of existing village health teams and interviewed ( [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Twelve women (40%) had completed education beyond primary school.…”
Section: Resultsmentioning
confidence: 99%
“…In vaginal birth, the amount of oxytocin increases in the maternal brain, which helps reduce stress and elevate feelings of happiness, and thus decreases the possibility of postpartum mental disorders . In addition, women who undergo cesarean may have less self‐confidence in parenting because they could not give birth naturally by themselves . Women who lack self‐confidence may feel nervous in parenting, which in turn is associated with distress, adjustment, and mood‐related mental disorders after childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the association between cesarean birth and postpartum mental disorders has been inconclusive and controversial . Nonetheless, the mechanisms that link cesarean birth and postpartum mental disorders proposed by researchers seem plausible, possibly because of decreased levels of oxytocin, maternal and neonatal physical problems, and low parental confidence …”
Section: Introductionmentioning
confidence: 99%